Yeast (Saccharomyces cerevisiae) Culture Promotes the Performance of Fattening Sheep by Enhancing Nutrients Digestibility and Rumen Development - Jie Wang; Guohong Zhao; Yimin Zhuang; Jianmin Chai; Naifeng Zhang (Fermentation, 2022)
Paraprobiotics are potential agents for improving animal health and performance. This experiment investigated the effect of dietary supplementation of yeast (Saccharomyces cerevisiae) culture (YC) on the growth performance, nutrient digestibility, rumen development and microbiome of fattening sheep. Ninety male Hu sheep weighed 38 ± 1.47 kg were randomly assigned to three treatments: CON diet (basal diet), LYC diet (basal diet supplied with 10 and 20 g/d yeast culture at the early and late stages, respectively), and HYC diet (basal diet supplied with 20 and 40 g/d yeast culture at the early and late stages, respectively). Treatments (LYC or HYC) were sprinkled on the feed surface according to the required dosage before feeding the basal diet to each sheep throughout the trial. The trial included early (60 days) and later (30 days) fattening periods. The results showed that average daily gain and feed efficiency were higher (p < 0.05) in the LYC group compared with CON in later and whole stages. Digestibility of DM, OM, CP, NDF and ADF were higher (p < 0.05) in LYC and HYC compared with CON. The retained N, the utilization efficiency of N and the biological value of N were higher (p < 0.05) in LYC compared with CON and HYC. Rumen NH3-N was higher (p < 0.05) in LYC and HYC. The papillary height of the rumen was higher (p < 0.05) in LYC when compared with CON and HYC, whereas rumen wall thickness and muscular layer thickness were higher (p < 0.05) in HYC compared with CON and LYC. The dressing percentage of LYC and HYC was higher (p < 0.05) compared with CON. The diversity, richness and structure of rumen microbiota showed no significant difference (p > 0.05); however, still observed remarkable increases in the relative abundance of several specific genera including Succiniclasticum and Fibrobacter with increasing doses of yeast culture. In addition, at the ASV level, ASV83, ASV123 (Succiniclasticum), and ASV148, ASV250 (Fibrobacter) were increased in YC groups. In conclusion, we confirmed that the supplementation of YC in diet could improve the growth and slaughter performance of fattening Hu sheep through improving nutrient digestion, especially nitrogen utilization, rumen microbial environment and the development of rumen epithelium, which proves the benefits of paraprobiotics in animal production.